A Novel Selectable Islet 1 Positive Progenitor Cell Reprogrammed to Expandable and Functional Smooth Muscle Cells. (28th March 2016) - Turner, Elizabeth C.; Huang, Chien-Ling; Sawhney, Neha; Govindarajan, Kalaimathi; Clover, Anthony J.P.; Martin, Kenneth; Browne, Tara C.; Whelan, Derek; Kumar, Arun H.S.; Mackrill, John J.; Wang, Shaohua; Schmeckpeper, Jeffrey; et al.
Abstract: Disorders affecting smooth muscle structure/function may require technologies that can generate large scale, differentiated and contractile smooth muscle cells (SMC) suitable for cell therapy. To date no clonal precursor population that provides large numbers of differentiated SMC in culture has been identified in a rodent. Identification of such cells may also enhance insight into progenitor cell fate decisions and the relationship between smooth muscle precursors and disease states that implicate differentiated SMC.  In this study, we used classic clonal expansion techniques to identify novel self-renewing Islet 1 (Isl-1) positive primitive progenitor cells (PPC) within rat bone marrow that exhibited canonical stem cell markers and preferential differentiation towards a smooth muscle-like fate. We subsequently used molecular tagging to select Isl-1 positive clonal populations from expanded and de novo marrow cell populations. We refer to these previously undescribed cells as the PPC given its stem cell marker profile, and robust self-renewal capacity. PPC could be directly converted into induced smooth muscle cells (iSMC) using single transcription factor (Kruppel-like factor 4) knockdown or transactivator (myocardin) overexpression in contrast to three control cells (HEK 293, endothelial cells and mesenchymal stem cells) where such induction was not possible. iSMC exhibited immuno- and cytoskeletal-phenotype, calcium signaling profile and contractile responses similar to bona fide SMC. Passaged iSMC could be expanded to a scale sufficient for large scale tissue replacement.  PPC and reprogramed iSMC so derived may offer future opportunities to investigate molecular, structure/function and cell-based replacement therapy approaches to diverse cardiovascular, respiratory, gastrointestinal, and genitourinary diseases that have as their basis smooth muscle cell functional aberrancy or numerical loss.